Poker and Betting - The Online Gambling Bill after Being Amended - Frańczuk, Magdalena; Knurowska, Iwona (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The study presents a reflection on the effects of changes in the Act of 19 November 2009 on gambling (Journal of Laws of 2009 No. 201, item. 1540, as amended). The paper highlights the key issues of a legal regulation on the clear statutory prohibition of organising and participating in online games such as poker, while allowing the possibility of organising and participating in online games, which are a form of betting. The main focus is on the impact of changes to the existing regulations on the activation of the shadow economy and tax revenues. The paper presents comparative legal mechanisms used on these issues under foreign laws of some West European countries.